2007 41st Annual Conference on Information Sciences and Systems 2007
DOI: 10.1109/ciss.2007.4298396
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Sampling of Bursty Signals by Level-Crossing - an Information Theoretical Approach

Abstract: Level-crossing analog-to-digital converters (LC ADC) have been studied in the literature and have been shown to efficiently sample certain classes of signals. In this paper we first characterize a class of bursty source signals. We then provide an information theoretical formulation that studies the application of LC ADC in data transmission in conjunction with compression. It is shown that compared to uniform sampling, LC sampling enables the same amount of information to be transmitted at substantially lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Level-crossing (LC) sampling has been proposed as an alternative to the traditional uniform sampling method [1][2][3][4][5][6][7][8][9][10]. In this approach, signals are compared with a set of reference levels and samples taken on the time axis, indicating the times at which the analog signal exceeded each of the associated reference levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Level-crossing (LC) sampling has been proposed as an alternative to the traditional uniform sampling method [1][2][3][4][5][6][7][8][9][10]. In this approach, signals are compared with a set of reference levels and samples taken on the time axis, indicating the times at which the analog signal exceeded each of the associated reference levels.…”
Section: Introductionmentioning
confidence: 99%
“…Higher instantaneous bandwidth/precision can be offered when sampling is performed, and resolution is improved without overall increase in bit rate or power consumption. It has been shown in [4,6,7] that by using LC sampling in communication systems, we can reduce the data transmission rate. For certain types of input, it has also been shown that LC performs advantageously in signal reconstructions, as well as in parameter estimations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher instantaneous bandwidth can be offered when LC sampling is performed, and resolution is improved without overall increase in bit rate or power consumption because the significant information in the bursty intervals is sampled. The data transmission rate can be reduced by using LC sampling in communication systems [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The random convolution based sampling strategy has been investigated by [7], [8] and [9] to solve this drawback. To avoid hardware realization challenges, we acquire less samples from analog signal directly by using Level-crossing (LC) sampling [10,11,12,13,14,15,16,17], in which an analog input signal is compared with a set of quantization levels (can also be called reference levels) and a sample is produced only when the input analog signal changes enough to cross a level, thus it results in nonuniform sampling and saves dynamic power in the analog-to-digital conversion (ADC) and following DSP for those powered by a very small battery and that involve "bursty" signals with varying activity over time, possibly including long periods of silence. Sampling by LC can mimic the behavior of such input signals.…”
Section: Introductionmentioning
confidence: 99%